A morphometric investigation of the small yellow croaker (Larimichthys polyactis Bleeker, 1877): evidence for subpopulations on the Chinese coast. (9th December 2015) - Zhang, C.; Jiang, Y.‐Q.; Ye, Z.‐J.; Li, Z.‐G.; Dou, S.‐Z.
Summary: In this study the morphometric characteristics based on the truss network system were constructed from the body shapes and used to investigate the population structure of the small yellow croaker ( Larimichthys polyactis Bleeker, 1877). From April to June 2013, a total of 431 fish samples were collected from commercial catches acquired with bottom trawlers (20 × 20 mm) in seven main spawning grounds along the coast of China. The results of principal component and discriminant function analyses indicated a clear distinction among the regional stocks and within the Haizhou Bay (HZB) stock. Observed differences primarily involved head measurements, body length and tail size, which were associated with environmental factors. Latitudinal gradient of the stock distribution and the relationship among the stocks provided further evidence for the existence of subpopulations and the re‐division of the East China Sea group. Moreover, the temporal inter‐structure of the HZB stock is a potential reason for the contrast in results from previous studies. Additional thorough studies of migration trajectories are required for a conclusive and improved understanding of the population structure.